The Copyright and Privacy Nexus - Frankel, Susy (Victoria University of Wellington Law Review, 2005)
The New Zealand development of a tort limited to wrongful publication of private fact (and in the United Kingdom by extension of breach of confidence) has not been accompanied by a consideration of the relationship that such a cause of action might have with intellectual property, particularly copyright. The emerging tort is potentially a strong right in information. The appropriate parameters of protection of information are core to many aspects of copyright law. This article questions whether the sidelining of copyright law in the privacy debate is appropriate. In general there is an overlap between intellectual property, particularly copyright and privacy in relation to information. Specifically an overlap arises because there is a section in the Copyright Act 1994 that provides a privacy right in relation to films and photographs. This article examines that provision and concludes that in its current form it is inconsistent with the emerging tort of privacy in wrongful disclosure of private information.